(untitled) (REMUNOM, 2025)
Abstract Children’s literature is an essential pedagogical tool for the educational and social development of children, contributing to the formation of critical and reflective readers. Their presence at school helps to improve reading, writing, and speaking skills, as well as promoting the interpretation of the world and the construction of values. By inserting children into narrative universes, literature allows them to recognize themselves in stories, stimulate their imagination and expand their perception of reality. Historically, children’s literature has evolved from narratives without a pedagogical focus to a resource that shapes behaviors and educates. In Brazil, its development was late, initially aimed at transmitting moral values, and only later gained an educational character. Today, it is understood as a central element in the formation of reading subjects and conscious citizens. The effective application of children’s literature faces challenges, such as inadequate teacher training, lack of pedagogical resources and school structure. These problems make it difficult to fully explore the stories and their multiple languages. However, by integrating literature into everyday school life, respecting children’s experiences, it is possible to humanize and enrich learning. In addition to books, resources such as songs, songs and games expand pedagogical possibilities, especially in different sociocultural contexts, such as in the state of Amazonas. Children’s literature, when well applied, transcends traditional teaching, transforming itself into an instrument of integral education. It not only teaches literacy, but also broadens horizons, building bridges between learning and social experience. Therefore, to fully take advantage of its potential, it is necessary to prepare mediators and create pedagogical materials that value narratives as tools for learning and social transformation, consolidating the importance of literature from the early school years. Keywords: Education; Children’s literature; Formation of the reader.